The classic horror stories - Lovecraft, H. P. (Howard Phillips) 1890-1937 (Oxford University Press, 2013)
H. P. Lovecraft (1890-1937) was a reclusive scribbler of horror stories for the American pulp magazines that specialized in Gothic and science fiction in the interwar years. He often published in Weird Tales and has since become the key figure in the slippery genre of "weird fiction." Lovecraft developed an extraordinary vision of feeble men driven to the edge of sanity by glimpses of malign beings that have survived from human prehistory or by malevolent extra-terrestrial visitations. The ornate language of his stories builds towards grotesque moments of revelation, quite unlike any other writer.